Interação entre híbridos de milho com controle químico de doenças foliares e influência na produtividade e qualidade química-bromatológica - Karlec, Fábio (2022)
The constant development of new corn hybrids inserts materials with productive characteristics adapted to the most different environments and with varied interactions with foliar diseases, fungicides and bromatological aspects. The different levels of susceptibility and control of fungal diseases which, in addition to interfering in the aspects of grain yield, can also influence the chemical-bromatological quality, since the use of corn as silage is of great importance in Brasil. livestock. The objective of this work was to evaluate the interaction of different corn hybrids with chemical control of foliar diseases and their influence on grain yield, dry matter and chemical-bromatological quality. The results of these works are presented in four chapters structured in an article. The first, with the objective of evaluating the susceptibility of corn hybrids to foliar diseases. The second, to evaluate different management programs for chemical control of foliar diseases in corn and their interactions with different levels of disease susceptibility. The third, with the objective of evaluating the influence of chemical disease control on grain yields and chemical- bromatological plant quality in silage corn hybrids. The fourth evaluated the effect of fungicide use on production and chemical quality in the absence of disease.